Accuracy improvement in embedded fiber Bragg grating interrogation systems - Wang Y. (2013)
This work reports a method to be used for the improvement of accuracy in fiber Bragg grating interrogation systems that operate with the tunable filter method or with a tunable laser signal. Since there may be an intrinsic nonlinearity in digital-to-analog converters (DAC) which produce the sweeping signal applied to the filter or laser, a calibration method, either by optical or electronic means would be required. While measuring temperature, the error in the proposed embedded interrogation of FBG sensors could reach 8°C without the nonlinearity correction. It is shown that the FPGA embedded system using a tunable filter driven by a DAC is able to correct the signal reducing the errors caused by non-ideal behavior of electronic components. © 2013 IEEE.